The Impact of Emerging Technology on Last Mile Delivery Operations - Martha Ingabire (Uganda Christian University, 2024)
The last mile delivery segment of logistics has witnessed a transformative evolution with the advent of emerging technologies. This dissertation explores the multifaceted impact of these technologies on last mile delivery operations, considering both the opportunities and challenges they present. Through a comprehensive review of literature, analysis of case studies, and empirical research, this study examines the adoption and integration of technologies such as autonomous vehicles, drones, robotics, and artificial intelligence in last mile delivery processes. The research delves into the efficiency gains, cost savings, and environmental benefits facilitated by these technologies, as well as their implications for workforce dynamics and urban infrastructure. Furthermore, it investigates the regulatory frameworks and ethical considerations shaping the deployment of emerging technologies in last mile delivery. By synthesizing theoretical insights with real-world insights, this dissertation contributes to a deeper understanding of the complex interplay between technology, logistics, and society. Ultimately, this study underscores the importance of strategic planning, collaboration, and adaptation in leveraging emerging technologies to optimize last mile delivery networks. It provides valuable insights and recommendations for industry stakeholders, policymakers, and researchers to navigate the dynamic landscape of modern logistics and harness the potential of technology-driven innovations for sustainable and efficient last mile delivery.